In-situ synthesis of aluminum/nano-quasicrystalline Al-Fe-Cr composite by using selective laser melting. (15th December 2018) - Kang, N.; El Mansori, M.; Lin, X.; Guittonneau, F.; Liao, H.L.; Huang, W.D.; Coddet, C.
Abstract: In this research, Al-Fe-Cr quasicrystal (QC) reinforced Al-based metal matrix composites were in-situ manufactured by using selective laser melting (SLM) from the powder mixture. The parametrical optimization based on our previous work was performed with focus on laser scanning speed. From the optimized parameters, an almost dense (99.7%) free-crack sample was fabricated with an ultra-fine microstructure. A phase transition from decagonal QC Al65 Cu25 Fe10 Cr5 to icosahedral QC Al91 Fe4 Cr5 could be observed as laser scanning speed decreases. Differential scanning calorimetry curves show that the QC phase is quiet stable until 500 °C. And then, the effects of annealing temperature on the microstructural and mechanical properties were determined. The results indicate that the recrystallization and growth behavior of α-Al grains could be prevented by QC particle during annealing. Furthermore, the growth of QC particle, which tends to form a porous structure, leads an improvement of Young modulus and decline of ductility. Graphical abstract: Image 1 Highlights: Pore and crack free Al/quasicrystal composite was fabricated by SLM from powder mixture. Melting, reaction and solidification behavior of quasicrystal was investigated. Quasicrystal morphology changes from pentagon to porous reticulate after annealing. Tensile strength and ductility decreases with the increment of annealing temperature.